A CONCEPTUAL PAPER ON SOFTWARE PLATFORM DEVELOPMENT TO ACHIEVE HEALTH MANAGEMENT - Jayabharathi, S; Appandairaj, A (IJRDO -Journal of Computer Science Engineering, 2015)
This paper aims to develop the architectural framework of software development on web services and integrate with communication technology. Proliferation of communication tools improves the standard of delivering healthcare to all section of people. Development of software on cloud environment and deploying the same in mobile platform to enhance the delivery of health care services. The conceptual layer develops the ontology section where the exchange of data and communication layer defines web services. TB is one of the deadly disease hampers India’s potential in achieving full healthcare to wider section of the people. It also weakens the country development agenda on human development index. The proposed framework here address this issue and bring out the possibility of real time implementation in achieving health care management in Tuberculosis. The integration of system architecture with mobile technology enables to facilitate frequent flow of communication for all stakeholders in this process and subsequently achieve overall strategy.